1992
DOI: 10.1080/02701367.1992.10608762
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Optical Density and Skinfold Measurements: Effects of Age and Level of Body Fatness

Abstract: We examined relationships between skinfold (SKF) and optical density (delta OD) measurements across age and levels of body fatness (%BF) for 151 women, 20 to 72 years. There were significant (p < .05) relationships between delta ODs and SKFs at all sites, except the thigh. The interaction (SKF x Age) was significant (p < .05) for pectoral and biceps delta ODs. Slope comparisons indicated the relationships for younger (29 years) and older (59 years) women differed significantly from zero and each other (p < .05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Limited research has been performed investigating the reliability of OD measures used with NIR. However, three studies have shown reliability for the biceps site to be very high at 0.95 (37), 0.96 (34), and 0.97 (13). These values are similar to those found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Limited research has been performed investigating the reliability of OD measures used with NIR. However, three studies have shown reliability for the biceps site to be very high at 0.95 (37), 0.96 (34), and 0.97 (13). These values are similar to those found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies reported by WILMORE et al, (1994) indicated that only the NIR reading from the biceps contributed significantly to the variance in percent body fat as measured by hydrostatic weighing. Several other studies (CONWAY et al, 1984;HORTOBAGYI et al, 1991;MCLEAN and SKINNER, 1992;QUATROCHI et al, 1992;EATON et al, 1993) have reported that the inclusion of multiple site readings did not improve NIR results. The study by found that the NIR results systematically overestimated percent body fat in subjects with less than 20.7% body fat and underestimated percent body fat in subjects with more than 20.7% body fat.…”
Section: Resultsmentioning
confidence: 98%
“…Η μέθοδος δερματοπτυχών βασίζεται στο συλλογισμό ότι το υποδόριο λίπος έχει υψηλή συσχέτιση με το συνολικό σωματικό λίπος (Quatrochi et al, 1992). Αρχή αυτής της τεχνικής είναι ότι το ποσό του υποδόριου λίπους είναι ανάλογο με το 50% του συνολικού ποσού του σωματικού λίπους.…”
Section: μέτρηση του σωματικού λίπουςunclassified